2017
DOI: 10.1192/bjp.bp.116.196345
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation and suicidal behaviour in adolescents and young adults: systematic review and meta-analysis

Abstract: Research suggests that lesbian, gay and bisexual (LGB) adolescents have a higher risk of suicidal behaviours than their heterosexual peers, but little is known about specific risk factors.To assess sexual orientation as a risk factor for suicidal behaviours, and to identify other risk factors among LGB adolescents and young adults.A systematic search was made of six databases up to June 2015, including a grey literature search. Population-based longitudinal studies considering non-clinical populations aged 12-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
89
2
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(106 citation statements)
references
References 58 publications
7
89
2
3
Order By: Relevance
“…38 Family discord and feelings of guilt, shame, fear, isolation and rejection are also reported and are associated with mental health problems. 39 We found that depressive symptoms began to decline from age 18 in the sample overall and more so in sexual minorities. This could be due to social and psychological changes such as increased independence or changes in peer groups that result from moving away perhaps.…”
Section: Sexual Orientation Was Measured With a Single Question Aboutmentioning
confidence: 58%
“…38 Family discord and feelings of guilt, shame, fear, isolation and rejection are also reported and are associated with mental health problems. 39 We found that depressive symptoms began to decline from age 18 in the sample overall and more so in sexual minorities. This could be due to social and psychological changes such as increased independence or changes in peer groups that result from moving away perhaps.…”
Section: Sexual Orientation Was Measured With a Single Question Aboutmentioning
confidence: 58%
“…Fifth, analyses according to sexual orientation were not performed and transsexual individuals were excluded. We are aware there are important suicidal risk differences among sexual minorities and we have reported some of them in a recent systematic review of the literature (Miranda‐Mendizábal et al, ). To assess these issues, a specific paper based on the UNIVERSAL project survey will be performed.…”
Section: Discussionmentioning
confidence: 99%
“…Results evidenced from 2.26 15 to 2.92 16 times higher rates of suicidality (ideation, intent, plans, attempts and serious attempts) in sexual minority individuals, a figure that became bigger with the increasing severity of suicidal behaviour.…”
Section: Introductionmentioning
confidence: 94%